Variations of the Nasal Septum in Adult Nigerians: Computed Tomography Study - Ominde, Beryl Shitandi; Ikubor, Joyce; Igbigbi, Patrick Sunday; Okolugbo, Nekwu (International Archives of Otorhinolaryngology, 2023)
Introduction The morphological variants of the nasal septum have been implicated in sinus pathology and pose a challenge during endoscopic surgeries.Objective The present study aimed at evaluating the prevalence of nasal septum variants in adult Nigerians.Methods The present study was performed at the Radiology Department of Delta State University Teaching Hospital, Nigeria, following ethical approval. Brain computed tomography (CT) scan images of 336 adults were evaluated for nasal septum variants. The angle of the deviated nasal septum was measured, and the severity was classified. Data were analyzed using IBM SPSS Statistics for Windows, version 23.0 (IBM Corp., Armonk, NY, USA). The angle of deviation was presented in means and standard deviation. Frequencies of the variants were presented in percentages. The Student t-test was used to compare the angle of deviation, while the chi-squared test was used to compare the frequencies in the different groups. A p-value < 0.05 was considered statistically significant.Results The prevalence of straight and deviated nasal septum was 59.5% and 40.5%, respectively. Deviation was predominant in females (46%) and, more frequently, of moderate severity (75%). The angle of deviation was significantly larger in males (12.55 ± 2.99°) than in females (11.13 ± 2.41°; p = 0.003). Nasal spur had a prevalence of 11.9%, and its coexistence with deviated nasal septum was observed in 5.06%. Septal pneumatization was seen in 10 patients (3%).Conclusion Deviation of the nasal septum occurred more in females and toward the left; however, the angle of deviation was significantly higher in males. Nasal septal spur and pneumatization were the least prevalent variants.
Keywords: nasal; septum; variation